Sentencing and criminal justice - Ashworth, Andrew (Cambridge University, 2013)
Examines English sentencing law in its context, drawing not only upon legislation and the decisions of the courts but also upon the findings of research and on theoretical justifications for punishment. This new edition has been extensively revised to integrate the new laws introduced by the Criminal Justice Act 2003.